MODELING MARINE OPERATIONS BASED ON INTELLIGENCE TREAT PREDICTION IN INDONESIAN NAVAL 2ND FLEET COMMAND USING MCDM - Okol Sri Suharyo; Budi Santoso Wiryo; Fa'iq Mumtaz Muhammad (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2020)
ABSTRACT Indonesia, which is an archipelago country, needs strong maritime sector security. Indonesian Navy in Law No. 34 of 2004 has been given the mandate to safeguard the sovereignty of the Republic of Indonesia. Indonesian Naval 2nd Fleet Command as the executing command and operational supervisor every year carries out the OMSP, which is carried out under the command of naval battle group (Guspurla) and marine security group (Guskamla). The importance of intelligent information regarding the estimated threat / contingency that will occur is very influential on decision makers in an operational planning and in the context of taking action against the contingency/threat. With the contingencies that have been given by the intelligence sector staff, it is necessary to have an appropriate marine operation modeling. In multi-operation operations, it is necessary to have a supporting attribute, namely a headquarters warship (C2). The purpose of this study is to formulate an operation modeling using the selection of a headquarter warship which is preceded by the prior determination of contingency priorities. This study uses MCDM which consists of MCDA and MCDO which uses the integration of the Delphi method, AHP, Fuzzy Weighting, Goal programming and integer linear programming. Based on the processing of Delphi and AHP in determining contingencies, there are 6 (six) contingency priorities in the order: National jurisdiction marine security got a value of 0,23792; the spread of the pandemic was 0,22492; VVIP security was 0,20416; security of vital objects was 0,15410 and violence at sea was 0,12923 while marine pollution was 0,04967. While in the selection of a headquarters warship that functions to coordinate warships in carrying out sector patrols using FWH and IGP, 1st warship was selected to be the headquarters warship (C2) with a value of 6,006; with the second priority 4thwarship, which was 6,652; 5th warship was 7,198; 2nd warship was 7,890 and 3rt warship of 8,763. While in the modeling, it is found that in a year there are 4 operations under 2nd Guskamla where the level of area is security obtained from the KRI (warship) assignment for ALFA operations is 152 with 4.963.600 Kl of fuel, KILO is to consume 8.104.200 Kl of fuel, MIKE is 59,13 with 765.079 of fuel and by consuming 425.906 Kl of fuel on INDIA operations get a level of safety area of 44,91. Keywords: MCDM, Contigency,headquarters warship.